Public Financial Management in Latin America : The Key to Efficiency and Transparency. (International Monetary Fund, 2016)
In recent years, the countries of Latin America have embraced reforms in public financial management and have made many important advances-however, many challenges remain. This book brings together IMF and IDB staff and representatives from 16 governments in the region to document these reforms, and to examine the experiences and lessons learned. It is a valuable resource for those looking at issues in public financial management.